2009
DOI: 10.1016/j.bbabio.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a cytochrome b559 Synechocystis 6803 mutant spontaneously generated from DCMU-inhibited photoheterotrophical growth conditions

Abstract: We identified a spontaneously generated mutant from Synechocystis sp. PCC6803 wild-type cells grown in BG-11 agar plates containing 5 mM Glu and 10 microM DCMU. This mutant carries an R7L mutation on the alpha-subunit of cyt b559 in photosystem II (PSII). In the recent 2.9 A PSII crystal structural model, the side chain of this arginine residue is in close contact with the heme propionates of cyt b559. We called this mutant WR7Lalpha cyt b559. This mutant grew at about the same rate as wild-type cells under ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Our results showed that H22K␣ mutant PSII core complexes gave rise to EPR signals (g z ϭ 6.11; g y ϭ 5.90), which are characteristic for the high spin form of cyt b 559 . These EPR signals were also observed in R7L␣ mutant PSII core complexes (36) and in PSII membranes treated with 2,3-dichloro-5,6-dicyano-p-benzoquinone (characterized with the g ϭ 6.19 and g ϭ 5.95 split signal) (37). It is generally believed that the high spin state (S ϭ 5/2) corresponds to a five-coordinate complex of Fe III PorL that has a square pyramidal structure where the Fe(III) ion is above the plane of the porphyrin (Ref.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Our results showed that H22K␣ mutant PSII core complexes gave rise to EPR signals (g z ϭ 6.11; g y ϭ 5.90), which are characteristic for the high spin form of cyt b 559 . These EPR signals were also observed in R7L␣ mutant PSII core complexes (36) and in PSII membranes treated with 2,3-dichloro-5,6-dicyano-p-benzoquinone (characterized with the g ϭ 6.19 and g ϭ 5.95 split signal) (37). It is generally believed that the high spin state (S ϭ 5/2) corresponds to a five-coordinate complex of Fe III PorL that has a square pyramidal structure where the Fe(III) ion is above the plane of the porphyrin (Ref.…”
Section: Discussionmentioning
confidence: 62%
“…Defects in the binding of extrinsic subunits in mutant PSII core complexes have been shown to influence the redox property of cyt b 559 (5). However, our results in Table 3 showed that H22K␣ and Y18S␣ mutant PSII core complexes contained much more LP form of cyt b 559 (ϳ79 and ϳ86%, respectively) than oxygen-evolving or Triswashed wild-type PSII core complexes (ϳ14 and ϳ30%, respectively) (36). Tris-washed wild-type PSII core complexes were depleted of all extrinsic polypeptides.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Lehetséges, hogy ezek az aminosav mutációk megváltoztatják a PBP kötődési affinitását, tehát azok a PSII komplexek, amelyek a D2' izoformát tartalmazzák más, valószínűleg gyengébb PBP horgonyzási képességgel bírnak. Kiemelnénk továbbá a Gln97Arg mutációt, ami a D2 fehérjének a cit b559 alegységével érintkező felületén található aminosav cseréje, melyet a PBP kapcsolódással szintén kapcsolatba hoztak (60,143). …”
Section: Az Eredmények Megvitatásaunclassified